2018
DOI: 10.17645/si.v6i3.1642
|View full text |Cite
|
Sign up to set email alerts
|

Returns to Human Capital and the Incorporation of Highly-Skilled Workers in the Public and Private Sector of Major Immigrant Societies: An Introduction

Abstract: Across the major immigrant societies of the European Union, EU-15 countries, migrants and minorities still experience economic disadvantage. This failure of economic integration poses significant questions about the utilization of human capital, the management of mobility and the competitiveness of European labour markets (Cameron, 2011;OECD, 2017). Using a variety of datasets, this special issue pushes the debate forward in several ways. We will consider the integration outcomes of both migrants and second ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Further consideration is necessary regarding the types of skills. In the literature on migration and labour market integration, education level is often used as a key indicator of human capital (Demireva and Fellini 2018). However, as Williams and Baláž (2005) have argued, formal education, and its translation into professional and economic outcomes, does not fully cover the diversity of skills which actually constitute 'total human capital' (Li et al 1996) and 'competences' (Evans 2002).…”
Section: Broadening the Concept Of Human Capitalmentioning
confidence: 99%
“…Further consideration is necessary regarding the types of skills. In the literature on migration and labour market integration, education level is often used as a key indicator of human capital (Demireva and Fellini 2018). However, as Williams and Baláž (2005) have argued, formal education, and its translation into professional and economic outcomes, does not fully cover the diversity of skills which actually constitute 'total human capital' (Li et al 1996) and 'competences' (Evans 2002).…”
Section: Broadening the Concept Of Human Capitalmentioning
confidence: 99%
“…At the same time, a growing body of research finds that general political interest and trust in government is high among immigrants. For instance, research in France finds higher levels of political interest among immigrants than among natives (Tiberj and Simon 2012), research in the United Kingdom similarly finds higher levels of political interest and trust in government among immigrants than among natives (Maxwell 2010; Heath et al 2013), and most of the immigrant groups examined in a recent study in Switzerland reported higher levels of social trust than native Swiss (Sanders et al 2014), despite lower rates of turnout for immigrants in all these countries. Whether this is because immigrants are referring to the sending country when answering questions on political interest, are positively selected on social trust, or because they have “voted with their feet” and thus perceive their new home more favorably when contrasted with the country they left behind, we expect a decoupling of political interest and voting behavior among the foreign born, with a weaker association between the two than observed among natives (H1A).…”
Section: Introductionmentioning
confidence: 99%
“…Research in the United States (Feliciano and Lanuza 2017), France (Ichou 2014), and Italy (Brunori, Luijkx and Triventi 2020) consistently finds a weaker association between parental and child educational attainment, which can be partially explained by the fact that absolute levels of educational attainment do not have the same meaning in terms of relative social standing across different sending countries. Applied to the case of political engagement, international migration disrupts all of the channels by which socioeconomic status is expected to shape the political socialization process: the background knowledge acquired in sending country school systems is unlikely to translate directly to the receiving country, the absolute level of education of immigrant parents, particularly those from less meritocratic or weaker educational systems, may be a weaker indicator of their own social background or genetic endowment, and finally due to general difficulties in transferring skills and widespread occupational downgrading among the foreign born (Demireva and Fellini 2018), parental educational attainment is likely to be a weaker indicator of their achieved social status in the receiving country. We, therefore, expect that the relationship between parental education and the political engagement of their children will be weaker in immigrant families than in families with native-born parents (H3) .…”
Section: Introductionmentioning
confidence: 99%